THE THE CORRELATION BETWEEN STUDENTS INTEREST AND ACADEMIC ACHIEVEMENT IN LEARNING ENGLISH - Goni, Rifanda; Muntuuntu, Meity; Sanger, Maikel (English Education Department, 2021)
This study focuses on students interest in English and how it influences students achievement The aim of this study is to figure out whether there is a correlation between students interest and their academic achievement in learning English The number of the sample in this research are 87 students at the second grade of SMA Negeri 1 Tomohon This study used quantitative research design which is non experimental research The data collected with questionnaire to obtain the information about students interest and students achievement in learning English The questionnaire consists of 31 items divided into positive and negative statements The items were tested with SPPS to determent the validity and the reliability of each items The data was analysed by using the formula of Pearson Product Moment Correlation It was found that the correlation score was 0 424 The significance value was 0 217 showed in the r table The score of correlation 0 424 was higher than the significance value 0 217 means that the alternative hypothesis was accepted Based on the result it can be concluded that there was a positive correlation between students interest and their academic achievement in learning English The researcher suggests that the case interest is very important particularly in affecting students achievement therefore it must be improved < p>